Analysis of Strengths and Difficulties in Adolescent Mental Health in Jayapura City: A Cross-Sectional Study - Pamangin, Lisda Oktavia Madu; Adimuntja, Natalia Paskawati; Izaac, Fransina Alfonsina (Lambung Mangkurat University, 2026)
Early detection of mental health problems among adolescents remains limited. This cross-sectional study aimed to analyze the mental health profiles of school-age adolescents and to compare mean rank scores for emotional, behavioral, hyperactivity, peer, and prosocial aspects by education level. The research was conducted from August to October 2024; subject were 397 adolescents aged 11–17 years from 12 secondary schools in four districts in Jayapura City. The results shows that only 51.1% of adolescents fell into the normal category for emotional problems. Significant differences were found in behavioral problems (p = 0.000) and prosocial behavior (p = 0.000) between junior high and high school students, whereas no significant differences were observed in emotional problems (p = 0.099), hyperactivity (p = 0.216), or peer problems (p = 0.511). These results highlight that behavioral and prosocial issues differ by education level, while emotional, hyperactivity, and peer issues do not. The study underscores the importance of early detection and targeted interventions to address behavioral and prosocial challenges among adolescents.